Islamic law of will for the administration of estates - Hj Ibrahim, Badruddin (IIUM PRESS, 2024)
This book deals with Islamic law of will for the administration of Muslim estate. It examines rules of Islamic law of wills in Malaysia in respect of testamentary provisions giving directions as to the administration of the estate and other matters. This is done in the context of the will of entrustment (wisoyah) in particular. The discussion focuses on the meaning of will of entrustment (wisoyah) its origin, its characteristic, its legality, its legal ruling and its creation which deal with four essential elements: testator (musi), executor (wasi), subject matter of will (musa fih) and formation (sighah). The discussion will also highlight the issues of testacy and intestacy with regard to Muslim estate. In what sense are these two terms to be taken by Muslim? The study attempts to examines various state enactments relating to Islamic law of wills. Some suggestions for amendment of the existing provisions or additional provisions will be made where the present law is unclear or inadequate. The emphasis is on writing an Islamic will that may be probated. This is necessary as the substantive law of wills is Islamic law but adjective law is civil law. This requires some reference to the meaning of Islamic wills as understood at present and wills under civil law.